Enhancing College Learners' Writing Skills through The Integration of ChatGPT: Strategies, Benefits, And Concerns - Soelistiyowati, Endang; Permatasari, Alfelia Nugky; Nugroho, Vincentius Tangguh Atyanto; Kusmulyadi, Alya Shalsabillah Febri (Makassar State University, 2024)
Abstract. Writing instructions pose challenges for educators, as students often struggle to effectively express their ideas in writing. First language influence further complicates the writing process. With the emergence of ChatGPT, this paper aims to explore its potential application in the writing classroom. This study investigates the strategies employed by students in integrating ChatGPT, an AI language model, into their writing process. Seven outstanding undergraduate students of the Applied English program preparing themselves for Indonesian International Student Mobility Awards (IISMA) were asked to write some simple essays. They are encouraged to utilize ChatGPT to help them improve their writing. Their portfolio of essays was used to explore how students utilize this technology to enhance their writing skills and evaluate the effectiveness of such integration. Some in-depth interviews were also conducted with these students who actively engaged with ChatGPT to understand how they enhance their writing skills through the help of ChatGPT: students' experiences and approaches to incorporating ChatGPT into their writing workflow, including idea generation, improving sentence structure and grammar, enhancing coherence and flow, and expanding vocabulary. Perceived benefits and challenges associated with integrating ChatGPT are examined, including: effects on confidence, efficiency, and writing quality. Concerns regarding overreliance, plagiarism, and authenticity of the written work are also addressed. This study's findings highlight the efficacy of integrating AI language models in writing classes through ChatGPT's writing suggestions, enhancing students' expression, structure, and style. Further the study shows that while ChatGPT improves students' writing skills , it raises concerns about overreliance and plagiarism. Ethical guidelines and long-term studies are needed to address dependency issues and maintain authenticity. Assessing ChatGPT's adaptability across writing contexts is crucial for responsible integration in education, advancing AI-assisted writing understanding. Keywords: college writing, ChatGPT, learning strategies